2015
DOI: 10.1017/s1431927615008752
|View full text |Cite
|
Sign up to set email alerts
|

Use of a hybrid silicon pixel (Medipix) detector as a STEM detector

Abstract: Scanning transmission electron microscopy has traditionally relied on the high angle annular dark field technique for imaging atoms [1,2], which provides a simple and easy to understand contrast, which is strongly related to atomic number. More recently, there has been a resurgence of interest in alternative imaging modes, including bright field [3,4] and annular bright field imaging [5,6]. Ultimately, however, the most flexible STEM experiment would be to record the entire back focal plane of the specimen ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In particular, later contributions demonstrated that the inner angle of ADF detectors had to be relatively high to exclude coherent diffraction from dominating the signal (Pennycook & Jesson, 1991;Hartel et al, 1996). Other refinements of this arrangement have been introduced over the years, including the use of split detectors for differential phase contrast (Dekkers & de Lang, 1977;Chapman, 1978;Chapman et al, 1990;McGrouther et al, 2014), multiple annular detectors (Shibata et al, 2010(Shibata et al, , 2017, and the use of bright field or annular bright field imaging (Hammel & Rose, 1995;LeBeau et al, 2009;Findlay et al, 2010;MacLaren et al, 2015). However, all these detector configurations integrate over large angular ranges of the back focal plane, resulting in the loss of most of the information contained in the diffraction pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, later contributions demonstrated that the inner angle of ADF detectors had to be relatively high to exclude coherent diffraction from dominating the signal (Pennycook & Jesson, 1991;Hartel et al, 1996). Other refinements of this arrangement have been introduced over the years, including the use of split detectors for differential phase contrast (Dekkers & de Lang, 1977;Chapman, 1978;Chapman et al, 1990;McGrouther et al, 2014), multiple annular detectors (Shibata et al, 2010(Shibata et al, , 2017, and the use of bright field or annular bright field imaging (Hammel & Rose, 1995;LeBeau et al, 2009;Findlay et al, 2010;MacLaren et al, 2015). However, all these detector configurations integrate over large angular ranges of the back focal plane, resulting in the loss of most of the information contained in the diffraction pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, building upon technologies developed for particle physics (Turala, 2005; Wermes, 2005; Turchetta et al, 2007; Delpierre, 2014), pixelated detectors developed for X-ray imaging have been adopted for electron imaging (Clough et al, 2014; McMullan et al, 2014; McGrouther et al, 2015; Tate et al, 2016; Mir et al, 2017; Tinti et al, 2018). Compared with charge coupled device (CCD)-based detectors, these direct electron detectors (DEDs) typically offer much lower noise levels, improved detector quantum efficiency (DQE), and modulation transfer function (MTF), some degree of radiation hardness, and crucially, fast readout of the images.…”
Section: Introductionmentioning
confidence: 99%
“…Just briefly, in the last decade these electron microscopes have greatly advanced by utilizing new hardware capabilities -such as correctors compensating aberrations present in electromagnetic lenses [41,51,81,96,131], monochromators compensating electron energy spread present in field emission electron guns [45,74,84,110,153,154], sensitive detectors to count even single electrons [13,50,100,101,122,133,151] -to enhance the spatial resolution in the sub-nm range, provide an energy resolution in the sub-eV range, and achieve a sensitivity to detect single atoms (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…This includes techniques such as electron energy loss spectroscopy and energy-dispersive X-ray spectroscopy, where these improvements have enabled the acquisition of large spectrum maps. A more recent development is the use of fast pixelated detectors for use in scanning transmission electron microscopy (pixelated STEM) [1], which allows for the acquisition of a large fraction of the STEM diffraction pattern for each probe position. These new developments enable new and exciting ways of characterizing materials, but also pose challenges with regards to handling large amounts of data.…”
mentioning
confidence: 99%